An Arduino-Driven Approach for Weight and Height Measurement Monitoring - Ade Firdaus; Nanda Ferdana; Rahmalisa Suhartina; Yusuf Borhanudin (Universitas Sam Ratulangi, 2023)
Abstract — The development of a weight and height measurement system based on Arduino has proven to be an effective tool for assessing body weight and providing valuable insights into individuals' health status. This system combines a proximity sensor and a digital scale to accurately measure weight and calculate the ideal body weight. The integration of buttons, an Arduino Uno, and an LCD 16x2 facilitates the operation and display of readings. Additionally, the system incorporates BMI calculation as a measurement guide, enhancing its functionality. The obtained results demonstrate the reliability and accuracy of the system in measuring weight and height. The device can be utilized not only in medical settings but also in fitness centers, households, and other environments where monitoring and maintaining optimal body weight is essential. By detecting overweight or underweight conditions, individuals can take necessary steps to prevent or manage weight-related health issues. In conclusion, the Arduino-based weight and height measurement system provides a practical and user-friendly solution for individuals to monitor their weight and obtain vital information regarding their ideal body weight. Further research and improvements can be made to enhance the system's capabilities, such as incorporating wireless connectivity for data transfer and analysis, enabling remote monitoring and tracking of weight trends. Keywords: Arduino, Berat Badan Ideal, BMI Calculation, Scales, Weight and Height Measurement, Wireless Connectivity, Body Weight Management